Poliomyelitis surveillance: the model used in India for polio eradication - Kaushik Banerjee; W. Gary Hlady; Jon K. Andrus; Sobhan Sarkar; John Fitzsimmons; Palitha Abeykoon (The World Health Organization, 2000)
Poliomyelitis surveillance in India previously involved the passive reporting of clinically suspected cases. The capacity for detecting the disease was limited because there was no surveillance of acute flaccid paralysis (AFP). In October 1997, 59 specially trained Surveillance Medical Officers were deployed throughout the country to establish active AFP surveillance; 11 533 units were created to report weekly on the occurrence of AFP cases at the district, state and national levels; timely case investigation and the collection of stool specimens from AFP cases was undertaken; linkages were made to support the polio laboratory network; and extensive training of government counterparts of the Surveillance Medical Officers was conducted. Data reported at the national level are analysed and distributed weekly. Annualized rates of non-polio AFP increased from 0.22 per 100 000 children aged under 15 years in 1997 to 1.39 per 100 000 in 1999. The proportion of cases with two adequate stools collected within two weeks of the onset of paralysis increased from 34% in 1997 to 68% in 1999. The number of polio cases associated with the isolation of wild poliovirus decreased from 211 in the first quarter of 1998 to 77 in the first quarter of 1999. Widespread transmission of wild poliovirus types 1 and 3 persists throughout the country; type 2 occurs only in Bihar and Uttar Pradesh. In order to achieve polio eradication in India during 2000, extra national immunization days and house-to-house mopping-up rounds should be organized.